Analisis Pemahaman Konsep Hukum Kekekalan Energi Mekanik Mahasiswa Tadris IPA Pada Mata Kuliah Energi Dalam Sistem Kehidupan - Windiyanti Rokmana, Arinta (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Physics is a branch of science that contains complex explanations regarding the relationships between various natural events which are expressed as facts, theories, concepts, principles and physical laws. Energy is one of essential chapter in physics which contains concepts that need to be understood not memorized. One of the topics discussed in energy material which includes many abstract concepts is the law of conservation of mechanical energy. Studying the law of conservation of mechanical energy, which contains abstract concepts, certainly requires conceptual understanding not just remembering and memorizing. Understanding concepts in physics is very important because it can help develop critical thinking skill, creative thinking skill, and good problem solving skill. The descriptive quantitative method with a test approach was used as a method in this study and the sample is 72 Tadris IPA college students of IAIN Ponorogo in the 3rd semester. The results of the study show that in the category of understanding the concept of the law of conservation of energy in objects moving vertically upwards was classified as moderate, in the category understanding the concept of the law of conservation of energy in objects moving along a certain path was classified as low.